2013
DOI: 10.1159/000353433
|View full text |Cite
|
Sign up to set email alerts
|

Fit and Motivated: Outcome Predictors in Patients Starting a Program for Lifestyle Change

Abstract: Background: In previous pilot studies we have demonstrated that the Treatment Motivation and Readiness Test (TRE-MORE) is capable of predicting the outcome of obesity therapy and that a higher muscle mass (MM) is associated with a greater weight loss. Purposes of the present study were: to confirm the predictive value of TRE-MORE scores and MM, using a standardized non-pharmacologic intervention for weight loss; to explore the relationship between TRE-MORE and MM; to discriminate predictors of attendance from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 11 publications
4
40
2
Order By: Relevance
“…In our study, this parameter, assessed through the TREMORE test [29], showed a lower predictive power than previously reported [11,29]. However, some methodological differences of these studies, compared to the present, should be highlighted: the population enrolled was more selected (i.e.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In our study, this parameter, assessed through the TREMORE test [29], showed a lower predictive power than previously reported [11,29]. However, some methodological differences of these studies, compared to the present, should be highlighted: the population enrolled was more selected (i.e.…”
Section: Discussioncontrasting
confidence: 83%
“…Those include male gender and younger age [9], and greater muscle mass [10,11]; conversely, patients with medical comorbidities, a history of repeated attempts at losing weight and with weight cycling, as well as those treated with drugs which induce weight gain, have a lower probability to succeed [6,7,12]. In contrast with the above mentioned results, Jackson et al [13] in a recent study found that being female, heavier and older predicted weight loss in the Health and Retirement Study (performed in the United States), whereas the same predictors did not reach statistical significance in the English Longitudinal Study of Ageing.…”
Section: Introductionmentioning
confidence: 99%
“…As already said, self-motivation has been considered as a predictor of success with consistent evidence [22] and the findings of Teixeira et al [22] are in agreement with earlier findings [27] and with more recent studies which reported an association of self-motivation with weight loss and weight loss maintenance (e.g., Cresci et al [32] ). Furthermore, motivational interviewing used to increase motivation for change and to improve treatment outcomes, appears to enhance weight loss in overweight and obese patients [33,34] .…”
Section: Self-motivationsupporting
confidence: 90%
“…The PCP has the unique advantage of seeing patients for various health concerns, creating many opportunities to address their weight issues [11]. Evidence shows that if health providers diagnose, recommend, and counsel clients about weight loss, patients will be more likely to follow a weight loss program [10,54,55]. Despite its well-established benefits, only 20-40% of primary care providers offer weight loss counseling to obese patients because of time constraints, inadequate knowledge, ill-prepared counseling skills, and difficulty explaining technical language [52].…”
Section: Pcp and Interventionmentioning
confidence: 99%
“…Since 1980, the rates of diabesity in the US have more than doubled; men of normal weight and without diabetes are now in the minority [1]. There is a lack of knowledge in the literature about what evidence-based approaches will help motivate overweight males to start and continue on a weight loss regimen [10]. Though the literature indicates that there are effective weight loss methods, there is often a lack of adequate attention and preparation from the primary care setting [11].…”
mentioning
confidence: 99%